2018
DOI: 10.1017/s0007114517003944
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D, calcium and parathyroid hormone levels in Native and European populations in Greenland

Abstract: Ca homoeostasis is important to human health and tightly controlled by powerful hormonal mechanisms that display ethnic variation. Ethnic variations could occur also in Arctic populations where the traditional Inuit diet is low in Ca and sun exposure is limited. We aimed to assess factors important to parathyroid hormone (PTH) and Ca in serum in Arctic populations. We included Inuit and Caucasians aged 50-69 years living in the capital city in West or in rural East Greenland. Lifestyle factors were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Although the current study by Andersen et al . ( 7 ) has documented higher 25(OH)D among Inuit than non-Inuit participants, as before ( 8 ) , the investigators have also found significantly lower serum Ca and PTH. Among the non-Inuit participants, as expected, PTH increased as 25(OH)D decreased, with an inflection between approximately 40 and 50 nmol/l, whereas there was no such trend among the Inuit participants.…”
Section: Beyond Vitamin D – Calcium Homoeostasis In Inuit and Non-inusupporting
confidence: 54%
See 2 more Smart Citations
“…Although the current study by Andersen et al . ( 7 ) has documented higher 25(OH)D among Inuit than non-Inuit participants, as before ( 8 ) , the investigators have also found significantly lower serum Ca and PTH. Among the non-Inuit participants, as expected, PTH increased as 25(OH)D decreased, with an inflection between approximately 40 and 50 nmol/l, whereas there was no such trend among the Inuit participants.…”
Section: Beyond Vitamin D – Calcium Homoeostasis In Inuit and Non-inusupporting
confidence: 54%
“…In their study among 50–69-year-old Inuit and non-Inuit adults in Greenland, Andersen et al ( 7 ) have extended their previous work on vitamin D status in Greenland residents by considering Ca homoeostasis and reporting analysis of serum parathyroid hormone (PTH) and Ca, as well as 25(OH)D concentrations and dietary habits. Previously, this team described determinants of circulating 25(OH)D among the 50–69-year-old adult demographic in the capital, Nuuk, and a town and remote settlement in East Greenland (both at approximately 65°N) ( 8 ) .…”
Section: Beyond Vitamin D – Calcium Homoeostasis In Inuit and Non-inumentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture risk differs with ethnicity, and ethnic differences in hip fractures risk between South African Blacks and Caucasians Whites were attributed to differences in hip geometry [1,2,3]. Similarly, ethnic differences exist between Inuit and Caucasians in bone metabolism [4] while hip geometry in populations in Greenland remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The powerful endocrine mechanisms that control bone mineralisation differ between Inuit and Caucasians [4].…”
Section: Introductionmentioning
confidence: 99%